Improved Vitamin B-6 Status Is Positively Related to Lymphocyte Proliferation in Young Women Consuming a Controlled Diet - Kwak, Ho-Kyung; Leklem, James E.; Hardin, Karin; Hansen, Christine M.; Shultz, Terry D. (The Journal of nutrition, 2002)
To examine the effect of increased intake levels of vitamin B-6 (B-6) on lymphocyte proliferation and interleukin 2 (IL-2) concentration, young women (n = 7) consumed a constant diet containing 1 mg (5.91 μmol) B-6/d for a 7-d adjustment period, followed by three 14-d experimental periods during which the daily B-6 intake was 1.5, 2.1 and 2.7 mg (8.86, 12.41 and 15.95 μmol)/d, respectively. Weekly fasting blood and daily 24-h urine samples were collected. Lymphocyte proliferation and IL-2 production were measured in response to phytohemagglutinin. Vitamin B-6 status improved with increased B-6 intake as measured by plasma pyridoxal 5′-phosphate (PLP) and urinary 4-pyridoxic acid. When subjects consumed 2.1 mg B-6/d for 7 d, lymphocyte proliferation increased by 35% (P ≤ 0.05) compared with the mean value after consumption of 1.5 mg B-6/d for 14 d. There was no further enhancement after an additional week of 2.1 and 2.7 mg B-6/d for 2 wk. Lymphocyte proliferation was correlated (P ≤ 0.01) with vitamin B-6 intake (r = 0.757), plasma PLP (r = 0.456) and erythrocyte aminotransferase activities (r = −0.361). Plasma IL-2 concentration and in vitro production did not change throughout the study, although five of seven subjects showed increases with intakes of 2.1 and 2.7 mg B-6/d, respectively, compared with the 1.5 mg/d intake. Concentrations of PLP in peripheral blood mononuclear cells were correlated (r = 0.357, P ≤ 0.01) with plasma PLP, but not with proliferation. These results show that improving vitamin B-6 status by consuming a B-6 intake higher than the current Recommended Dietary Allowance enhances lymphocyte proliferation.